Vascular plants of the headwaters of the Gocta, Chinata and Yumbilla waterfalls, Amazon region, Peru - Santa Cruz Cervera, Lázaro; Museo de Historia Natural, Universidad Nacional Mayor de San Marcos, Av. Arenales 1256, Jesús María, A.P. 14-0434, Lima. UNMSM, Programa de Estudios Generales, Área de Ciencias de la Salud. Calle Germán Amézaga N° 375. Lima 1 (2020)
We present here the diversity of vascular plants from the headwaters of the Gocta, Chinata and Yumbilla Falls, Amazonas region, Peru, 2012. 107 families, 279 genera and 509 species of vascular plants were registered. Pteridophyta presents 19 species in 14 genera and 10 families, Pinophyta, one species; and Magnoliophyta, 489 species in 264 genera and 96 families of this last division; 324 species, 194 genera and 80 families are included in the Magnoliopsida class and 165 species, 70 genera and 16 families are in the Liliopsida class. The Orchidaceae family is the most diverse, with 26 genera and 83 species, followed by the Asteraceae families, with 38 genera and 69 species and Poaceae, with 15 genera and 34 species. The most diverse genera are Epidendrum, with 25 species, followed by Peperomia and Solanum, with 11 species each. 54 species are endemic. The Asteraceae family is the one with the highest endemism, with 13 species (24.07%), followed by Orchidaceae, with 8 species (14.81%), Gentianaceae and Melastomataceae, with 5 species and 9.26% each. The species protected by national and international legislation (Appendix II CITES) are 84 species, with Orchidaceae, with 83 species, including the 8 most endemic species, the most representative family, and one species in the Cyatheaceae family. The species protected by D.S. 043-2006-AG are 11.